Penurunan Gejala Risiko Perilaku Kekerasan Melalui Acceptance and Commitment Therapy (ACT) di RSUD Tombulilato - Firmawati Firmawati; Andi Nur Aina Sudirman; Rona Febriyona (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2022)
Background: Violent behavior is one of the symptoms that becomes a reason for families to treat clients in mental hospitals because of the risk of endangering themselves and others. Acceptance Commitment Therapy (ACT) is a specialist nursing action given to clients with violent behavior.Purpose:  The purpose of this study was to determine the effect of Acceptance and Commitment Therapy (ACT) on symptom reduction with the risk of violent behavior at Tombulilato Hospital.Method: The research design used a quasi-experimental design with one group pre and posttest. The number of respondents in this study, namely patients with violent behavior amounted to 18 respondents at Tombulilato Hospital.Result: From the results of the study, it was found that there was an effect of Acceptance and Commitment Therapy (ACT) on the reduction of symptoms with the risk of violent behavior at the Tombulilato Hospital. The conclusion in this study was that the average behavior of respondents before ACT was carried out at Tombulilato Hospital was 1.611 with a standard deviation of 0.50 while the average behavior of respondents after ACT was carried out at Tombulilato Hospital was 1.1667 with a standard deviation of 0.38. Statistical results obtained p value = 0.007 (p < 0.05),Conclusion: it can be concluded that there is an effect of Acceptance and Commitment Therapy (ACT) on symptom reduction with the risk of violent behavior in RSUD Tombulilato